2011
DOI: 10.1128/jvi.01862-10
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-Zoster Virus Transcriptome in Latently Infected Human Ganglia

Abstract: Varicella-zoster virus (VZV) is an exclusively human, neurotropic alphaherpesvirus. Primary infection typically produces chickenpox (varicella), after which virus becomes latent in cranial nerve ganglia, dorsal root ganglia, and autonomic ganglia along the entire neuraxis (16). Decades later, virus reactivation results in shingles (zoster), frequently complicated by chronic pain (postherpetic neuralgia) as well as stroke (VZV vasculopathy), paralysis and incontinence (VZV myelopathy), and blindness (VZV progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 34 publications
3
64
1
4
Order By: Relevance
“…We found that VZV-infected human neurons in cell culture transcribed every annotated ORF, unlike the limited viral transcription present in human and monkey ganglia latently infected with varicella-zoster virus (8)(9)(10). This confirmed a significant difference in virus gene transcription in vitro from that in human neurons latently infected with VZV.…”
supporting
confidence: 51%
“…We found that VZV-infected human neurons in cell culture transcribed every annotated ORF, unlike the limited viral transcription present in human and monkey ganglia latently infected with varicella-zoster virus (8)(9)(10). This confirmed a significant difference in virus gene transcription in vitro from that in human neurons latently infected with VZV.…”
supporting
confidence: 51%
“…Finally, we evaluated whether patient cells exhibited impaired ability to control VZV replication. VZVinfected MeWo cells were cocultured with PBMCs from controls or each of the 4 patients, and we measured expression of viral Orf63, which is among the most abundant viral transcripts (36). Consistent with the impaired IFN responses to VZV by PBMCs from P1, P3, and P4, we observed that VZV infection in MeWo cells gave rise to significantly higher viral gene expression when cocultured with PBMCs from P1, P3, or P4.…”
Section: Induction Of Ifns By At-rich Dna In Human Pbmcs Is Pol Iii-dmentioning
confidence: 56%
“…Both VZV 63 and VZV gE proteins were found exclusively in neurons, but not in nonneuronal cells. Importantly, transcripts corresponding to VZV ORFs 21, 29, 62, 63, and 68 (gE) are present in latently infected human ganglia (1,19). VZV gE is also present in vivo months after experimental infection of human dorsal root ganglia (22).…”
Section: Discussionmentioning
confidence: 99%
“…This is because increasing numbers of VZV transcripts are now being detected with more advanced technologies (19), and the exact extent of viral gene expression is still unknown in latently infected human ganglia. In parallel with our continuing studies of VZV latency in human ganglia, this promising neuronal model will be used to analyze the total degree of VZV transcription and translation and will also be used to attempt to reactivate virus from nonproductively infected neurons.…”
Section: Discussionmentioning
confidence: 99%